2004
DOI: 10.1023/b:caco.0000036152.58271.5e
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Drug Use and The Risk of Prostate Cancer (Canada)

Abstract: Our results suggest that BBs and long-term use of ABs may prevent PC whereas calcium channel blockers or angiotensin-converting enzyme inhibitors do not influence PC risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 28 publications
6
141
2
1
Order By: Relevance
“…There are studies that suggest that a-blockers may have some role in the development of prostate cancer, 20,21 but there are no studies relating this polymoprhism, antihypertensive treatment, and cancer. Furthermore, the GenHAT interaction result diminished when adjusted for cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that suggest that a-blockers may have some role in the development of prostate cancer, 20,21 but there are no studies relating this polymoprhism, antihypertensive treatment, and cancer. Furthermore, the GenHAT interaction result diminished when adjusted for cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate and breast cancer cell lines, epinephrine (important in acute and chronic stress) reduced the sensitivity of cancer cells to apoptosis through interaction with ADRB2 receptors followed by protein kinase A-dependent BAD phosphorylation [60]. Although large-scale human studies are lacking, a recent epidemiological study showed a decreased incidence of prostate cancer in patients who took beta-blockers regularly thereby implying the importance of the activation of β-adrenergic receptors on the development of prostate cancer [61].…”
Section: Cell Survivalmentioning
confidence: 99%
“…74 Another study concludes that b blockers may produce a general decrease in cancer risk, 75 and a second study found a decrease in prostate cancer rate with b blocker use. 76 On the other hand, a few studies have shown that use of b blockers either has no effect on the rate of breast cancer 77,78 or may even increase it. 79 Any NE level lowering or receptor blocking drug could potentially lower rates of carcinogenesis in humans, and this hypothesis is immediately testable through epidemiological investigation of medical records of large numbers of people who have taken these drugs.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…And when examining whether NE drugs affect cancer rates, it is not only important to compare people who are taking these drugs for a condition such as hypertension with healthy control subjects (some of whom may be taking these drugs), but also with hypertensive people taking classes of drugs that do not affect the NE system. 76 If NE is indeed an etiological factor in various types of cancer through activation of its extracellular receptors, drugs that affect its level or block its receptors may have an additive or synergistic preventative effect when paired with existing cancer preventing drugs that may have independent mechanisms of action, such as tamoxifen or anastrozole. 81 In a rodent model, estradiol has been shown to interact with the NE system in a manner that is thought to contribute to carcinogenesis.…”
Section: Literature Search Detailsmentioning
confidence: 99%